2021
DOI: 10.3892/ijmm.2021.4981
|View full text |Cite
|
Sign up to set email alerts
|

RepSox effectively promotes the induced differentiation of sheep fibroblasts into adipocytes via the inhibition of the TGF‑β1/Smad pathway

Abstract: Previous reports have demonstrated that RepSox can function as a replacement for cMyc and Sox2 in the reprogramming of cells into induced pluripotent stem cells (iPSCs), as well as increasing the levels of bone morphogenetic protein (BMP)-3 and inducing the phosphorylation of Smad1 in mouse embryonic stem cells. In the present study, it was demonstrated that RepSox caused the visible morphological transformation of sheep fibroblasts; however, no significant alterations in cell proliferation, apoptosis or chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Therefore, inhibition of GSK3-β by Wnt signaling could promote self-renewal and cell reprogramming by regulating the stability of c-Myc (40,44). Inhibition of TGF-β could induce mesenchymal to epithelial transition (MET) and increase Nanog expression (36). Together with the present findings, it may be concluded that cR could promote the reprogramming process by simultaneously inhibiting GSK3-β and TGF-β signaling.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Therefore, inhibition of GSK3-β by Wnt signaling could promote self-renewal and cell reprogramming by regulating the stability of c-Myc (40,44). Inhibition of TGF-β could induce mesenchymal to epithelial transition (MET) and increase Nanog expression (36). Together with the present findings, it may be concluded that cR could promote the reprogramming process by simultaneously inhibiting GSK3-β and TGF-β signaling.…”
Section: Discussionsupporting
confidence: 70%
“…At day 2 post-transduction, REFs were re-plated on an irradiated Oricell ® ICR mouse embryonic fibroblast feeder layer (cyagen Biosciences, Inc.). The following day, the culture medium was replaced with dMEM/F-12 supplemented with 10% KnockOut Serum Replacement (Gibco; Thermo Fisher Scientific, Inc.), 0.1 mM β-mercaptoethanol, 1% NEAA, 2 mM L-glutamine, 100 U/ml penicillin and 0.1 mg/ml streptomycin, which was further supplemented with 3 µM CHIR99021 (Sigma-Aldrich; Merck KGaA), 1 µM RepSox (Selleck Chemicals) and 15 ng/ml fibroblast growth factor 2 (R&D Systems, Inc.) on day 4 (36,37). The GFP + /iPS-like colonies [rat iPScs induced by OcT3/4, Sox2, Klf4, c-Myc, Nanog and Lin28 + cR (RiPScs-6F/cR)] were mechanically picked 20-30 days after viral transduction and re-cultured on feeder layers.…”
Section: Culture Of Refsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported to induce brown adipogenesis 44 and promote the differentiation of sheep fibroblasts into adipocytes 45 . RepSox induction of contractile markers in SMCs was found to depend on activation of NOTCH signaling pathway 27 .…”
Section: Discussionmentioning
confidence: 99%
“…RepSox functions as a selective TGFβR-1/ALK5 inhibitor which inhibits ALK5 autophosphorylation 42 and was used to reprogramming of fibroblasts into iPSCs by replacing cMyc and Sox2 43 . Recently, it was reported to induce brown adipogenesis 44 and promote the differentiation of sheep fibroblasts into adipocytes 45 . RepSox induction of contractile markers in SMCs was found to depend on activation of NOTCH signaling pathway 27 .…”
Section: Discussionmentioning
confidence: 99%